Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
810-89-88
= 88(82-81-80)
= 88.55 chia hết cho 55
Vậy 810-89-88
810 - 89 - 88 = 88.(82 - 8 - 1) = 88.55 chia hết cho 55
chọn mk nha
810 - 89 - 88
= 88 . (82 - 8 - 1)
= 88 . (64 - 8 - 1)
= 88 . 55 chia hết cho 55
810 - 89 - 88
=> 88 . ( 82 - 8 - 1 )
=> 88 . ( 64 - 8 - 1)
=> 88 . 55 chia hết cho 55
a) Ta có:
\(8^{10}-8^9-8^8=8^8.\left(8^2-8-1\right)=8^8.55⋮55\)
\(\Rightarrow8^{10}-8^9-8^8⋮55\)
b) Ta có:
\(10^9+10^8+10^7=10^7.\left(10^2+10+1\right)=10^7.111⋮111\)
\(\Rightarrow10^9+10^8+10^7⋮111\)
a) 810 - 89 - 88 = 88(82 - 8 - 1) = 88.55 chia hết cho 55
b) 817 - 279 - 913 = (34)7 - (33)9 - (32)13 = 328 - 327 - 326 = 326(32 - 3 - 1) = 326.5 = 324(32.5) = 324.45 chia hết cho 45
c) 109 + 108 + 107 = 107(102 + 10 + 1) = 107.111 = (27.56)(5.111) = 27.56.555 chia hết cho 555
810 - 89 - 88 =88 (82 -8-1)=88 x 55 chia hết cho 55
810-89-88
= 88.(82-8-1)
= 88.(64-8-1)
= 88.55 ⋮ 55